2015
DOI: 10.1016/j.lindif.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Does numerical processing uniquely predict first graders’ future development of single-digit arithmetic?

Abstract: Keywords:longitudinal design numerical processing arithmetic development fact retrieval The present longitudinal study investigated whether children's numerical processing skills at the start of formal schooling predict subsequent development in single-digit arithmetic and fact retrieval. At the start of first grade, we administered measures of numerical processing (digit naming, symbolic numerical magnitude comparison, nonsymbolic numerical magnitude comparison) as well as measures of intellectual ability, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 53 publications
10
45
0
1
Order By: Relevance
“…In addition, similar results have also been reported by researchers from studies that used other forms of magnitude comparison tasks (e.g., Holloway & Ansari, 2009; Kolkman et al, 2013; Lonnemann et al, 2011; Mundy & Gilmore, 2009; Sasanguie et al, 2012; Vanbinst et al, 2015). For example, in a recent study Vanbinst et al (2015) tried to explore the relationship between numerical magnitude comparison ability and simple arithmetic ability in first- and second-grade children using a computerized version of the magnitude comparison task. The researchers (Vanbinst et al, 2015) used accuracy and reaction time as indices to measure both symbolic and non-symbolic magnitude comparison.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, similar results have also been reported by researchers from studies that used other forms of magnitude comparison tasks (e.g., Holloway & Ansari, 2009; Kolkman et al, 2013; Lonnemann et al, 2011; Mundy & Gilmore, 2009; Sasanguie et al, 2012; Vanbinst et al, 2015). For example, in a recent study Vanbinst et al (2015) tried to explore the relationship between numerical magnitude comparison ability and simple arithmetic ability in first- and second-grade children using a computerized version of the magnitude comparison task. The researchers (Vanbinst et al, 2015) used accuracy and reaction time as indices to measure both symbolic and non-symbolic magnitude comparison.…”
Section: Discussionsupporting
confidence: 86%
“…However, these researchers reported contrasting results (see Chen & Li, 2014; De Smedt et al, 2013 for a review). While a number of researchers have found significant correlations between non-symbolic numerical comparison (dot arrays) and arithmetic skills (e.g., Bonny & Lourenco, 2013; Halberda, Mazzocco, & Feigenson, 2008; Inglis, Attridge, Batchelor, & Gilmore, 2011; Linsen, Verschaffel, Reynvoet, & De Smedt, 2014; Mazzocco, Feigenson, & Halberda, 2011; Mundy & Gilmore, 2009; Vanbinst, Ghesquière, & De Smedt, 2015), other have not (e.g., Holloway & Ansari, 2009; Kolkman, Kroesbergen, & Leseman, 2013; Lonnemann, Linkersdörfer, Hasselhorn, & Lindberg, 2011; Mundy & Gilmore, 2009; Nosworthy et al, 2013; Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013; Sasanguie, Van den Bussche, & Reynvoet, 2012; Soltész, Szűcs, & Szűcs, 2010; Vanbinst, Ghesquière, & De Smedt, 2012). Furthermore, a large number of studies have reported significant correlations between symbolic numerical comparison (Arabic digits) and arithmetic abilities (e.g., Holloway & Ansari, 2009; Kolkman et al, 2013; Lonnemann et al, 2011; Mundy & Gilmore, 2009; Nosworthy et al, 2013; Sasanguie et al, 2012; Vanbinst et al, 2015); however, a smaller number of studies did not find these significant relationships (e.g., Sasanguie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The current cross-sectional data also do not allow us to establish predictive associations between symbolic number comparison and mathematics achievement. Some studies have indeed shown that symbolic number comparison predicts future mathematics achievement (De Smedt et al, 2009) and math development (Vanbinst et al, 2015), yet these predictive associations need to be studied across larger ageranges in longitudinal studies, in which also bidirectional associations should be considered. The current paper-andpencil measure allows one to study these associations on a large-scale level.…”
Section: Discussionmentioning
confidence: 99%
“…The question arises which competencies should be assessed when designing screening measures to identify these at-risk children. Research has pointed to the importance of numerical magnitude processing, or people's elementary intuitions about numerical magnitudes, for the development of mathematics achievement as children's understanding of numerical magnitudes correlates with (e.g., Holloway &Ansari, 2009) andpredicts (e.g., De Smedt, Verschaffel, &Ghesquière, 2009;Halberda, Mazzocco, & Feigenson, 2008;Mazzocco, Feigenson, & Halberda, 2011;Vanbinst, Ghesquière & De Smedt, 2015) individual differences in mathematics achievement (De Smedt, Noël, Gilmore, & Ansari, 2013, for a narrative review; Schneider et al, 2016, for a meta-analysis).…”
Section: Introductionmentioning
confidence: 99%
“…In general, authors agree that numeracy performance in the early childhood years adequately predicts later mathematics performance (Jordan, Glutting & Ramineni 2010). Especially magnitude comparison, number reading, counting skills, basic arithmetical skills, number line acuity, spontaneous focusing on numerosity and numeracy-related logical knowledge have been found to be relevant for later mathematics performance (Aunio & Niemivirta 2010;Friso-van den Bos et al 2015;HannulaSormunen, Lehtinen & Räsänen 2015;Jordan et al 2010;Krajewski & Schneider 2009;LeFevre et al 2010;Nguyen et al 2016;Passolunghi, Vercelloni & Schadee 2007;Toll et al 2015;Vanbinst, Ghesquière & De Smedt 2015). Related to the development of mathematical skills in early childhood years, there is an agreement among the researchers that children have biologically primary non-verbal number sense which is the base that children start to learn to use their number word sequence skills first in rhymes and then in enumeration tasks and from that follows the basic strategies for addition and subtraction problem solving (Jordan et al 2010;Mazzocco, Feigenson & Halberda 2011).…”
Section: Early Numeracy Skills Relevant For Later Mathematics Learningmentioning
confidence: 96%